The Factors Contributing to the Social Inequality among the Community of Ranto Panyang Timur, West Aceh - Arfriani Maifizar; Sopar Sopar; Erizar Erizar; Fenecia Fenecia; Mahamadaree Waeno (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2022)
Social processes that result in social migration often result in various social problems, such as disintegration between residents and immigrants. With the research context of the village of Ranto Panyang Timur Aceh Barat District, this research has the purpose to describe the phenomena of inequality suffered by the fishermen community who are relocated to a new village after the tsunami earth-quack disaster and describing the factors influencing the inequality and discrimination. Applying the descriptive qualitative method this study found that the process of social inequality in the coastal fishermen community at Ranto Panyang Timur Village proceed since they came to that village, and the forms of the inequality are neglect and discrimination in the context of social treatment and service from Keuchik (the head of the village) and his official staff. The factors that affect the social inequality between the indigenous residents and the fisherman who were relocated at Ranto Panyang Timur Village, West Aceh Regency were the least committed Keuchik’s, unresponsive village officials, and unfair treatment by the village officials in terms of services, and provide aid to the people who were relocated at Ranto Panyang Timur Village.